Value co-creation features: an empirical case study of B2B collaboration and interactions in New Zealand. Issue 3 (5th June 2020) - Rashid, Yasir; Tanveer, Anisha; Shaukat, Zeeshan; Sadiq, Imran
Abstract : Purpose: This paper aims to highlight four features of value co-creation among actors in a business-to-business environment. Service-dominant (S-D) logic of marketing is used as a theoretical lens to view at the process of value co-creation. Design/methodology/approach: Using an interpretive methodological approach, the authors collected empirical material from a single case based in New Zealand. The case was based on the collaboration, interaction and relationship between vendor and client during an information and communication technology (ICT) systems integration project. The unit of analysis was "points of value creation." Empirical material came from observation, in-depth interviews and documents such as meeting notes and email logs. Interpretation highlighted four features of the value co-creation process: motivators, outcomes, disadvantages and management. Moreover, personal and network aspects of value co-creation process emerged. Findings: The findings of this study capture benefits, as well as conflicts and frustrations, in a value co-creation process. Furthermore, it provides future research motivations for researchers currently working to develop S-D logic of marketing. Originality/value: It is suggested that there is relatively little direction on how value co-creation process should be undertaken in different contexts such as retail, education, health care and ICT. There is a need to understand the dynamics and specification of value co-creation process, as the literature is scarce in this field.